2023
DOI: 10.1590/fst.96122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coffee and cocoa as fermentation additives on sensory quality and chemical compositions of cigar tobacco leaves

Abstract: Exogenous additives applied for cigar tobacco leaves fermentation played an important role in sensory quality of cigar. In this study, effects of additives including coffee and cocoa on the quality of cigar tobacco leaves were explored. The changes of sensory quality, conventional chemical components, nonvolatile organic acids, and aroma compositions in tobacco leaves were studied. Results showed that the richness, mellowness and matureness of aroma, as well as the fluentness and sweetness of smoke in cigar we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Sensory analysis is a common method to evaluate food quality (Cai et al, 2022;Hu et al, 2022;Lopes et al, 2021;Zhang et al, 2021). The sensory evaluation of eggs was performed in the sensory analysis laboratory in Jimei University with the temperature of 22 °C and humidity of 60%.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Sensory analysis is a common method to evaluate food quality (Cai et al, 2022;Hu et al, 2022;Lopes et al, 2021;Zhang et al, 2021). The sensory evaluation of eggs was performed in the sensory analysis laboratory in Jimei University with the temperature of 22 °C and humidity of 60%.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Alkaloids, on the other hand, are a speci c type of chemical compound that are often responsible for the psychoactive effects. Some of the most common alkaloids found in cigar leaves include nicotine, anabasine, and nornicotine (Hu et al 2023). Consequently, the degradation of these molecules may play a signi cant role in the metabolic pathway of microorganisms during cigar production.…”
Section: )mentioning
confidence: 99%
“…The cigar production process mainly includes agricultural fermentation of tobacco leaves, industrial fermentation, rolling, and aging. Among them, aging is especially important for improving the quality of cigar tobacco leaves (Zheng et al 2022; Hu et al 2023). Since the preparation environment of cigar tobacco leaves is relatively mild, a large number of active enzymes and microorganisms are retained after rolling.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols are the main VFCs in CTLs as revealed via gas chromatography−mass spectrometry (GC−MS) results. 8,10,11 Solid-phase microextraction (SPME)-based GC−MS studies have shown that 3-methylvaleric acid, acetic acid, 3-neneneba acetylpyridine, dienicotine, and dihydroactinidiolide are the main compounds present in CTLs. 11−14 Gas chromatography−ion mobility spectrometry (GC− IMS) is a detection technology that combines the high separation ability of GC and the rapid response of IMS.…”
Section: Introductionmentioning
confidence: 99%
“…VFCs such as alcohols, alkenes, ketones, heterocycles, phenols, esters, and acids were detected in CTLs. Alcohols are the main VFCs in CTLs as revealed via gas chromatography–mass spectrometry (GC–MS) results. ,, Solid-phase microextraction (SPME)-based GC–MS studies have shown that 3-methylvaleric acid, acetic acid, 3-neneneba acetylpyridine, dienicotine, and dihydroactinidiolide are the main compounds present in CTLs. …”
Section: Introductionmentioning
confidence: 99%